Prospects for the Use of Monofocal IOLs with Extended Depth of Focus (EDOF) Instead of Traditional Multifocal (Trifocal) IOLs in Cataract Surgery - M. E. Konovalov; A. V. Morenko (Oftalʹmologiâ)
Purpose — a literature review of comparative studies of the clinical efficacy of IOLs based on extended depth of focus technology (EDOF) and trifocal IOLs (TFIOLs). Methods. Literature analysis was performed in the international database “PubMed”.The search keywords were “IOL with extended depth of focus (EDOF)”, “Trifocal IOL”, “Contrast sensitivity”, “Aberrometry”, “Defocus curve”. The choice of sources for the review was carried out in accordance with the criteria for prospective or retrospective studies. A total of 158 sources were analyzed, further using systematic review filters and the authors’ knowledge of the topic. The duration of the retrospective analysis was 8 years (2015–2022), some of the considered works were dated 2023. Results. The values of visual acuity for distance, near and at an intermediate distance in both studied groups did not differ significantly. When analyzing the defocusing curve, the preservation of visual acuity under load conditions from +1.0 to +3.0 diopters was determined for both types of IOL, respectively. At the same time, visual acuity was significantly better in the TPIOL group than in the EDOF group in the optical load range from -2.5 to -4.0 diopters. Most studies did not report significant difference between EDOF and TFIOL in terms of contrast sensitivity, the likelihood of postoperative “halo” effects, and “independence” of spectacle correction. The stated provisions are fully consistent with the results of the medical and technical evaluation of EDOF presented in the literature. Conclusion. The development of a new type of EDOF IOL seems to be a promising direction in cataract surgery, especially taking into account the possibility of using patients whose professional activities are associated with long-term visual work at intermediate distances (for example, users of personal computers). Further accumulation of clinical material is required in the context of the role and place of EDOF in the general system of aphakia correction, taking into account the IOL model and the conditions of the patient’s professional visual activity.